Preparation of low-dimensional materials for plasmonic bio-sensing - Das, Chandreyee Manas (Nanyang Technological University, 2022)
Nano-bio-photonics is a unique blend of three primary disciplines namely nanotechnology, biological sciences and optics. Surface plasmons are free electron density waves that are a result of the photons interacting with the free electrons that reside on the surface of noble plasmonic metals like Gold (Au) and Silver (Ag). The field of plasmonic bio-sensing falls under this domain.